1998
DOI: 10.1126/science.280.5371.1928
|View full text |Cite
|
Sign up to set email alerts
|

Call Duration as an Indicator of Genetic Quality in Male Gray Tree Frogs

Abstract: The "good genes" hypothesis predicts that mating preferences enable females to select mates of superior genetic quality. The genetic consequences of the preference shown by female gray tree frogs for long-duration calls were evaluated by comparing the performance of maternal half-siblings sired by males with different call durations. Offspring of male gray tree frogs that produced long calls showed better performance during larval and juvenile stages than did offspring of males that produced short calls. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
272
1
5

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 426 publications
(282 citation statements)
references
References 16 publications
4
272
1
5
Order By: Relevance
“…Recent studies that have adopted artificial fertilization techniques have provided some of the most compelling evidence to date for the good-genes hypothesis (Welch et al 1998;Barber et al 2001;Parker 2003;Sheldon et al 2003). Among these, Sheldon et al (2003) reported that under certain predation conditions sire coloration (and therefore presumably male attractiveness) influenced the susceptibility of juvenile moorfrogs to predation by water beetles.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies that have adopted artificial fertilization techniques have provided some of the most compelling evidence to date for the good-genes hypothesis (Welch et al 1998;Barber et al 2001;Parker 2003;Sheldon et al 2003). Among these, Sheldon et al (2003) reported that under certain predation conditions sire coloration (and therefore presumably male attractiveness) influenced the susceptibility of juvenile moorfrogs to predation by water beetles.…”
Section: Discussionmentioning
confidence: 99%
“…This condition dependence can be continuous (e.g. call duration in male grey tree frogs [48]) or a discrete polymorphism (e.g. sexually dimorphic mandible growth in stag beetles [53]).…”
Section: Why Do Phenotypically Plastic Resource Allocation Strategiesmentioning
confidence: 99%
“…Females from both lekking and non-lekking species were shown to present consistent preferences for certain male phenotypic traits (e.g. Doucet & Montgomerie 2003), and evidence that preferred males produce offspring that is more viable (Petrie 1994;Welch et al 1998) suggests that such traits are in fact indicators of male quality. While the adaptive value of particular 'good' genes is likely to be strongly environment-dependent (Zhou et al 2008), high heterozygosity is generally beneficial to individuals and has been associated with increased fitness across a wide range of species, including in wild and nonisolated populations (Brown 1997;Coltman & Slate 2003).…”
Section: Introductionmentioning
confidence: 99%